2017
DOI: 10.1186/s12871-016-0297-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of admission fascia iliaca compartment blocks on post-operative abbreviated mental test scores in elderly fractured neck of femur patients: a retrospective cohort study

Abstract: BackgroundPost-operative cognitive impairment is common in elderly patients following surgery for hip fracture, with undertreated pain being an important etiological factor. Non-opioid based analgesic techniques, such as nerve blocks, may help reduce the risk of cognitive complications. The aim of this study was to investigate whether receiving a fascia iliaca compartment block (FICB) as part of a pre-operative analgesic regime increased the odds of high post-operative abbreviated mental test scores (AMTS) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Outcomes showed that FICB had the highest probability of being the most effective against delirium. In a retrospective study comprising 959 patients aged over 65 years with a femoral neck fracture, Odor et al [ 62 ] investigated potential influence of FICB on postoperative abbreviated mental test scores (AMTS). Outcomes revealed that FICB use at admission was linked to significantly higher adjusted odds for a higher AMTS relative to lower AMTS than conventional analgesia method.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes showed that FICB had the highest probability of being the most effective against delirium. In a retrospective study comprising 959 patients aged over 65 years with a femoral neck fracture, Odor et al [ 62 ] investigated potential influence of FICB on postoperative abbreviated mental test scores (AMTS). Outcomes revealed that FICB use at admission was linked to significantly higher adjusted odds for a higher AMTS relative to lower AMTS than conventional analgesia method.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Inadequate analgesia has also been shown to negatively affect a patient’s AMTS, and regional analgesia has been found to reduce the risk of AMTS deterioration perioperatively. 15 Following hip fracture, patients with impaired cognition are less likely to return to their own homes or have successful rehabilitation. 1 Furthermore, hip fracture patients with delirium have been found to experience increased length of hospital stay and increased 1-year mortality, 5 and delirium superimposed on dementia is a strong predictor of functional dependence, institutionalization, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The AMTS is commonly used in Northern Ireland in the clinical setting 14 and has also been used in numerous studies assessing change in cognitive function among hip fracture patients. For example, Odor et al compared the impact of regional anesthesia on pre- and postoperative AMTS, 15 and Tahir et al used the AMTS on admission to assess baseline cognitive function when screening for postoperative delirium. 5 Thus, it has been suggested that, due to its brevity and sensitivity, the AMTS is a very useful screening test for elderly trauma patients to assess for impaired cognition of any cause.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of delirium increases with limited treatment of pain, so it is essential to provide good pain management [23]. Intermittent fascia iliaca compartment block (FICB) may reduce the incidence of delirium in patients with an intermediate risk of delirium [24] and preoperative FICB may also improve postoperative cognitive status [25]. Research indicates that nerve block is a good choice for pain control, especially in patients with cognitive impairment, as they have reduced abilities to describe their pain and their need for analgesia [26].…”
Section: Introductionmentioning
confidence: 99%